The Pathogenesis of Autism - Timothy John Watts (SAGE Publishing, 2008)
Autism is well known as a complex developmental disorder with a seemingly confusing and uncertain pathogenesis. The definitive mechanisms that promote autism are poorly understood and mostly unknown, yet available theories do appear to focus on the disruption of normal cerebral development and its subsequent implications on the functional brain unit. This mini-review aims solely to discuss and evaluate the most prominent current theories regarding the pathogenesis of autism. The main conclusion is that although there is not a clear pathway of mechanisms directed towards a simple pathogenesis and an established link to autism on the symptomatic level; there are however several important theories (neural connectivity, neural migration, excitatory-inhibitory neural activity, dendritic morphology, neuroimmune; calcium signalling and mirror neurone) which appear to offer an explanation to how autism develops. It seems probable that autism's neurodevelopmental defect is 'multi-domain' in origin (rather than a single anomaly) and is hence distributed across numerous levels of study (genetic, immunopathogenic, etc.). A more definitive understanding of the pathogenesis could facilitate the development of better treatments for this complex psychiatric disorder.